2018
DOI: 10.1002/cam4.1584
|View full text |Cite
|
Sign up to set email alerts
|

CD31‐labeled circulating endothelial cells as predictor in anlotinib‐treated non‐small‐cell lung cancer: Analysis on ALTER‐0303 study

Abstract: Our previous studies revealed that the level of activated circulating endothelial cells (aCECs) was correlated with the progression‐free survival (PFS) in antiangiogenesis therapy. Anlotinib displayed affirmatory efficacies in several clinical trials of non‐small‐cell lung cancer (NSCLC). To find a marker predicting the efficacy of anlotinib treatment, we investigated the correlations of aCECs with PFS and overall survival (OS) in patients with NSCLC treated with anlotinib and the impact of anlotinib on human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 36 publications
0
30
0
Order By: Relevance
“…[ 10 ] The CD31-labeled activated circulating endothelial cell is a potential indicator for predicting the efficiency of anlotinib in NSCLC, although it requires further validation. [ 11 ] CEA of the present patient seems to be an informative indicator of anlotinib because the change of serum CEA was to some extent parallel with the radiographic changes of the pulmonary lesions. More reliable biomarkers such as circulating DNA which is capable of predicting and monitoring the response to anlotinib require further validation.…”
Section: Discussionmentioning
confidence: 57%
“…[ 10 ] The CD31-labeled activated circulating endothelial cell is a potential indicator for predicting the efficiency of anlotinib in NSCLC, although it requires further validation. [ 11 ] CEA of the present patient seems to be an informative indicator of anlotinib because the change of serum CEA was to some extent parallel with the radiographic changes of the pulmonary lesions. More reliable biomarkers such as circulating DNA which is capable of predicting and monitoring the response to anlotinib require further validation.…”
Section: Discussionmentioning
confidence: 57%
“…Nowadays, the potential predictive biomarkers of anlotinib are still unclear, and identifying the ideal predictive efficacy biomarkers with which to screen the patient population will maximize the benefits to patients. In NSCLC, Liu et al 18 found CD31-labeled activated circulating endothelial cells (aCECs) could be used as a sensitive marker for the efficacy of anlotinib. Another study suggested serum levels of KLK5 and L1CAM had preferable predictive value for anlotinib response in NSCLC patients receiving third-line treatment.…”
Section: Discussionmentioning
confidence: 99%
“…As same as previous procedure, other 7 plasma samples (patient No. [8][9][10][11][12][13][14] from responders at baseline mixed together as a duplicate for protein extraction (Supplementary Table 1 and Supplementary Table 3). Therefore, we prepared two mixed samples from responders at baseline for proteomics analysis.…”
Section: Plasma Collection and Processingmentioning
confidence: 99%
“…Importantly, we thought that next generation sequencing (NGS) for plasma cell free DNA (cfDNA) plays a role in anlotinib responsive strati cation, and found that the biomarker tumor mutation index (TMI) plus IDH1 exon4 mutation status can signi cant stratify the anlotinib responders [11]. In addition, other recent studies introduced predictors including CD31-labeled circulating endothelial cells and baseline characteristics of patients, for the strati cation of those patients treated with anlotinb [12,13]. Due to complex architecture of anlotinib anti-angiogenic signaling pathway [14], as far as possible screen biomarker from omics analysis will contribute to multiple cancer (NSCLC, SCLC, RCC, and so on) treatments with anlotinib.…”
Section: Introductionmentioning
confidence: 99%